An investigation into graduation used in advertising of cosmetics in english and vietnamese (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The thesis aims at investigating Graduation used in advertising of cosmetics in English and Vietnamese in form of the syntactic features of phrases, in semantic view of Appraisal Theory as well as in pragmatic view of Speech Acts. The study is both quantitative and qualitative. The data for analysis in this thesis were 300 samples of slogans of advertising cosmetics (150 in English and 150 in Vietnamese) obtained from websites and magazines of well-known cosmetic companies in the world and in Vietnam. The thesis focused on analysing and contrasting Graduation used in advertising of cosmetic in English and Vietnamese. The findings obtained from the data analysis revealed that Graduation used in advertising of cosmetics were syntactically found in form of noun phrases, verb phrases, adjective phrases as well as adverb phrases. Semantically, the result of the data analysis showed Ggraduation wereas used in advertising of cosmetics in English and Vietnamese as modes of force and of focus. Additionally, Ggraduation was pragmatically found in boosting illocutionary force of representative and of directive in advertising of cosmetics in English and Vietnamese. The study also pointed out the similarities and differences between Graduation used in advertising of cosmetics in English and Vietnamese in terms of syntactic and semantic features. Hopefully, the results of the study will lead some mentioned implications and suggestions to practical applications for teaching and learning English